Photoluminescence in the CaXSr1-xWO4 system at room temperature - Porto, S. L.; Longo, Elson [UNESP]; Pizani, P. S.; Boschi, T. M.; Simoes, L. G. P.; Lima, S. J. G.; Ferreira, J. M.; Soledade, L. E. B.; Espinoza, J. W. M.; Cassia-Santos, M. R.; Maurera, M. A. M. A.; Paskocimas, C. A.; et al. (Academic Press Inc. Elsevier B.V., 2008)
In this work, a study was undertaken about the structural and photoluminescent properties, at room temperature, of powder samples from the Ca(x)sr(1-x)WO(4) (x = 0-1.0) system, synthesized by a soft chemical method and heat treated between 400 and 700 degrees C. The material was characterized using Infrared, UV-vis and Raman spectroscopy and XRD. The most intense PL emission was obtained for the sample calcined at 600 degrees C, which is neither highly disordered (400-500 degrees C), nor completely ordered (700 degrees C). Corroborating the role of disorder in the PL phenomenon, the most intense PL response was not observed for pure CaWO4 or SrWO4, but for Ca0.6Sr0.4WO4. The PL emission spectra could be separated into two Gaussian curves. The lower wavelength peak is placed around 530nm, and the higher wavelength peak at about 690nm. Similar results were reported in the literature for both CaWO4 and SrWO4. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: tungstates; scheelite; photoluminescence; disorder